Questionnaire of Students’ Responses in Use Google Classroom: Validity and Reliability Tests - Ardini, Ni Wayan (Universitas Pendidikan Ganesha, 2021)
The phenomenon of using Google Classroom as an E-learning platform in implementing online teaching and learning activity during pandemics has been appearing. Based on the phenomena, students’ response toward the use of Google Classroom as an online platform in learning English was investigated in this study. In preparing a valid and reliable items questionnaire the writer was conducted a try-out items questionnaire. The criteria valid; if r count > r table while, items questionnaire is reliable if items questionnaire has Cronbach’s Alpha value > 0.60. The result of validity items is 27 items was analyzed only 26 items questionnaire was valid and 1 item not valid because this item has valuer count < 0.312 that is 0.245. The result of reliability showed 26 items from 4 dimensions were analyzed and all items are reliable and consistent because it has Cronbach Alpha value > 0.60. After the questionnaire was distributed to the sample hopefully data were gaining validity and reliability.